'Making time': Long-distance marriages and the temporalities of the transnational family. (March 2019) - Acedera, Kristel Anne; Yeoh, Brenda SA
By focusing on the relations of intimacy between migrant wives working in Singapore and their left-behind husbands living in the Philippines, this article investigates how transnational couples negotiate the liminalities and temporariness embedded in the experience of labour migration. Using the timescales of migration as a conceptual frame, the article analyses the mutual, if uneven, shaping of marital relationships at the micro-timescale of transnational family time and the meso-timescale of Singapore's labour migration regime. It focuses on how 'doing family' across distance is centrally facilitated through the affordances of communication technologies to create rhythms and manage ruptures. These technologies are crucial in (re)making domestic family time in the transnational household. The way the micro-temporalities of transnational family life are reorganised works in tension with how couples negotiate liminal conditions imposed by Singapore's work permit and pass system. The article argues that temporariness and precarity, which deter the imagination of a stable future, are constantly negotiated in the lives of the transnational family through different temporal strategies. By bracketing off intense emotions and downplaying ruptures in relationships, the transnational family is able to focus on their future aspirations of achieving their projects through migration. As migration timelines are indefinitely extended and family separation is prolonged, the transnational family strives to endure through these strategies of (re)making their temporalities.